УПРАВЛЕНИЕ ИННОВАЦИОННЫМИ ПРОЕКТАМИ: ПРИНЦИПЫ И МЕТОДЫ ОЦЕНКИ РИСКОВ - R. S. Aitelenov; A. A. Karaneev (Экономика: стратегия и практика, 2018)
For optimal control for the processes of innovation projects management, a theoretical and practical base based on study and improving of existing theories and practices is necessary. The goal of the paper is study of approaches in the field of innovation projects management. The paper considers the interpretation of “innovation project” term, stages and principles of innovation projects management, methods of estimation of risks and effectiveness of innovation projects, its positive and negative sides. In addition, the research considers the main key moments of innovative development of Kazakhstan, the attention is paid to approved innovation projects. The conclusion describes the existing positive moments and weak sides of innovation policy in Kazakhstan. The following work methods were used: scientific analysis and synthesis, induction and deduction, analysis of statistical data, and graphical analysis. The results of the work can be used to determine the tasks of the innovation policy of the State to prepare and manage the innovation projects.